An overview of conservative treatment for lower back pain. (June 2011) - Balaguéé, Federico; Dudler, Jean
This article summarizes the available evidence on the management of patients with subacute or chronic low back pain. The largest part is devoted to nonspecific low back pain but the models of spinal stenosis and disk herniation/sciatica are also specifically addressed. The authors point out the limited evidence available and the importance of a tailored approach for the individual patient. As the effect sizes of most therapies are rather small (close to that of a placebo), patients'' preferences and other variables important for individualized management are highlighted. The task for the practitioner is difficult and awareness of this is important. Some speculation regarding potential future ways of improving patient care are presented.